Gambaran Hasil Pemeriksaan Sifilis Pada Homoseksual - Rianto, Muh. Rifo; Basarang, Mujahidah; Nurhidayat, Nurhidayat; Arham, Chaerul; Astari, Afrina Suci (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
One of the sexually transmitted infections is syphilis which is caused by the bacterium Treponema palidum which can be transmitted through sexual intercourse and direct contact with the patient's body fluids. Homosexuality is sexual attraction in the form of disorientation of a sexual partner, namely a person's tendency to engage in sexual behavior with the same sex. Sexual intercourse carried out by homosexuals can be at risk of sexually transmitted diseases. The purpose of this study was to determine the transmission of syphilis to homosexuals. The method of this research is observation with the accidental sampling technique of 50 samples using the immunochromatographic examination method. The results of the study showed that out of 50 samples, 14 samples were positively infected with syphilis. So it can be concluded that homosexuals are at high risk of contracting the sexually transmitted disease syphilis